Spatial pattern and associated factors of HIV testing and counselling among youths (15-24 years) in Ethiopia - Adugnaw Zeleke Alem; Alemneh Mekuriaw Liyew; Habtamu Alganeh Guadie (BMC, 2021)
Abstract Background HIV testing and counseling (HTC) services are key for HIV prevention, treatment, care, and support. Although the prevalence of HIV infection is high among adolescents and young adults, evidence suggests the utilization of HTC service among youth is very low in Ethiopia. Identifying factors and the geographic variation of HTC uptake is important to prioritize and design targeted prevention programs to increase its utilization and reduce HIV infection in hot spot areas. Methods Data from the 2016 Ethiopian Demographic and Health Survey were used to analyze 10,781 youth aged 15-24 years. The spatial analysis was performed in ArcGIS 10.1. The Bernoulli model was used by applying Kulldorff methods using the SaTScan software to analyze the purely spatial clusters of HTC uptake. A multilevel logistic regression analysis was used to identify the associated individual and community-level factors of HTC uptake and estimate between community variance. All models were fitted in Stata version 14.0 and finally, the adjusted odds ratio (AOR) with a corresponding 95% confidence interval (CI) were reported. Results In this study, the spatial patterns of HTC uptake were found to be non-random (Global Moran's I = 0.074, p value< 0.001). Forty-seven primary clusters were identified that were located in the entire Somali region with a relative likelihood of 1.50 and the Log-Likelihood Ratio of 135.57. Youth who were ever married (AOR = 4.65; 95% CI; 4.05, 5.34), those attended higher education (AOR = 3.97; 95% CI; 3.10,5.08), those from richest household (AOR = 1.86; 95% CI; 1.44, 2.39), aged 20-24 years (AOR = 2.25; 95% CI; 2.02,2.51), having compressive HIV related knowledge (AOR = 2.05; 95% CI; 1.75,2.41), and exposed to media (AOR = 1.38; 95% CI; 1.22,1.57) were positive association with HTC uptake. However, being male (AOR = 0.81; 95% CI; 0.73,0.91) and having high HIV related stigma (AOR = 0.53; 95% CI; 0.42,0.67) were negatively associated with HTC uptake. At the community-level, youth from communities with a high percentage of educated (AOR = 1.45; 95% CI; 1.17,1.80) were more likely to utilize HTC compared with those from communities with low percentages of educated. Conclusion The current study indicated differences in HTC uptake in the country. Both individual and community-level factors affected HTC uptake in Ethiopia. Multifaceted intervention approaches that consider individual and community factors are required to improve HTC uptake.